ASEAN CAPITAL MARKET INTEGRATION DURING THE COVID-19 PANDEMIC - Winisudo, Christian Kevin; Wijaya, Hendra (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
This research aims to test whether there is a contagion effect on capital markets in ASEAN-5 countries during the COVID-19 pandemic in 2020 and 2022. The research took samples based on the closing prices on the Indonesia Stock Exchange (IHSG), Malaysia Stock Exchange (FTSE), Singapura Stock Exchange (STI), Stock Exchange of Thailand (SET), and Philippine Stock Exchange (PSEI) index for 3 years starting in 2020 and ending in 2022 using the documentation method. This research is quantitative research based on the empirical testing of data. This research uses the contagion effect method, which aims to see the effects of risk transmission that can occur when a shock or crisis occurs in a capital market. The results show that there was a contagion effect on the capital markets in ASEAN-5 countries for 3 years during the COVID-19 pandemic. Apart from that, the contagion effect that occurs in the ASEAN-5 capital market shows that the capital markets in ASEAN are interconnected with each other so that if a problem occurs in one capital market, the effects can be felt and spread to the capital markets of other ASEAN countries. The COVID-19 pandemic spread and had an impact on capital markets in ASEAN-5 due to the relationship or integration between their capital markets.